5 - - + -(x + y - z) = -x - y + z What do brackets do? Something on the outside of a bracket will affect the terms in the bracket.--+-(x + y - z)=-x - y + z
6 Removing BracketsIf we can remove brackets from expressions, then we can simplify expressions with multiple brackets by collecting like terms. Expressions can also be referred to as polynomials (unless they go on forever).For example, 1 + x + x2 + … + x∞ is not a polynomial.
7 (3x+4y)+(2x-5y) = 3x+4y+2x-5y = 5x-y Example Simplify… Oh, no change! This is because both pairs of brackets have a + sign in front of them.=5x-yNice and easy!
8 (3x+4y)-(2x-5y) = 3x+4y-2x+5y = x+9y Example Simplify… Ahh… Because of the minus symbol in front of the second bracket, the operators swapped…=x+9yA little more confusing!
9 -(3x+4y)+(2x-5y) = -3x-4y+2x-5y = -x-9y Example Simplify… It doesn’t matter which bracket has a minus symbol, those terms’ + or – symbols will swap.=-x-9y
10 -(3x+4y)-(2x-5y) = -3x-4y-2x+5y = -5x+y Example Simplify… As both sets of brackets have a “-” in front of them, all + and – symbols have swapped.=-5x+y
11 5x-y x+9y -x-9y -5x+y Answers Doesn’t that seem strange? Look at the answers!5x-yx+9yDoesn’t that seem strange?-x-9y-5x+y
12 WorksheetPlease complete the questions on the worksheet provided.